Utilization of Pepeta, a locally processed immature rice-based food product, to promote food security in Tanzania - Miraji, Kulwa F. (PLoS One, 2021)
Consumption of pepeta, a traditionally processed immature rice product, is common in Tanzania, where it contributes to food security as an early rice food i.e. when there is no other food available at the household while the crops in the field not yet fully ripe. Many production steps are needed to guarantee a consistent, good quality pepeta product, and this hinders its utilization in other rice-growing sub-Saharan regions. This study aims to gain insight into the pepeta processing knowledge and final product, and assess variations in the processing conditions and parameters across the study area. A survey among 257 Tanzanian processors and consumers revealed that the pepeta product is widely known, rated second (73.5% respondents) as rice-based food after wali (cooked white rice, (100%)) and linked to traditions of the communities in the study area. Harvest of immature rice grain, roasting, pounding, cleaning, and packing are the main process steps of pepeta production. Method of rice harvest, rice suitability for pepeta production after optimum harvest, dryness of grains and number of pounding as indicator to terminate roasting and pounding process respectively, and packaging materials used varied significantly across respondents in the study area. Reported criteria considered by respondents for product acceptability did not vary significantly across study area. The criteria include colour (76.5%), general appearance (60.8%), texture (64.7%) and taste (52.9%). Immature rice paddy and pepeta were sold at a higher price than mature rice paddy and white rice, respectively, which implies that options to facilitate pepeta processing through, for instance, standardization of processing conditions and parameters could lead to increased income.